Production performance and egg quality of breed chickens fed a diet containing turmeric extract (Curcuma domestica) in their drinking water - Dini widianingrum; Rachmat Somanjaya; Oki Imanudin; Irvan Fujiyanto; Nurul Iman Syarifudin (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
This study aimed to analyze the effect of turmeric extract (Curcuma domestica) supplementation in drinking water on the production performance and egg quality of Isa Brown laying hens (Gallus gallus domesticus). A completely randomized design (CRD) was applied with 60 Isa Brown layer-phase hens, five treatments (P0: 0%, P1: 1%, P2: 2%, P3: 3%, P4: 4% turmeric extract), and four replicates. Data were analyzed using ANOVA followed by Duncan’s multiple range test. The results showed that turmeric extract supplementation had a significant effect (P<0.05) on Feed Conversion Ratio (FCR), water intake, and Hen Day Production (HDP). The lowest FCR was observed in P2 (2.35 ± 0.26), the highest HDP in P1 (69.75 ± 11.58%), and water intake decreased as turmeric extract concentration increased, with P0 showing the highest intake (7,132.50 ± 187.68 mL). Turmeric extract also significantly improved (p<0.05) egg weight, albumen thickness, and Haugh units. The highest egg weight was recorded in P4 (68.58 g), while the best albumen thickness (7.38 mm) and Haugh units (82.31) were found in P3. Feed intake, body weight gain, yolk percentage, albumen percentage, eggshell percentage, yolk thickness, eggshell thickness, and egg index were not significantly affected (p>0.05). It is concluded that turmeric extract supplementation at 3% in drinking water produces the best overall egg quality, while 4% yields the highest egg weight.